Evaluating the role of CD44 in oral squamous cell carcinoma and potentially malignant disorders – An immunohistochemical study - Tharani V; Nandhini Gunasekaran; Rajkumar Krishnan; Swaathi R; Vasanthi V (Oral Oncology Reports)
Background: Oral squamous cell carcinoma (OSCC) accounts for 84–97 % of all cases of oral cancer. Oral submucous and leukoplakia are examples of potentially malignant disorders (PMDs) that are signs of the preclinical stage of oral cancerCD44 (Cluster of differentiation) is a cell surface glycoprotein that serves as a Cancer Stem Cell marker. Aim: The purpose of the study was to look at the presence of CD44 immunohistochemically in oral epithelial dysplasia, oral submucous fibrosis, and OSCC and how it influences a patient's prognosis. Materials and methods: In this retrospective study, the expression of CD44 were evaluated in 60 paraffin –embedded specimens (20 OSCC, 20 Dysplasia, 20 OSMF). This study was evaluated by spss 21. Differences in the mean number of CD 44-positive cells per field among epithelial dysplasia, oral submucous fibrosis and squamous cell carcinomas were assessed using one-way ANOVA and comparison between the groups were analysed by using Bonferroni post hoc test. Statistical significance was at P < 0.05. Results: On comparing the CD44 immuno-expression, the highest expression was seen in OSCC followed by dysplasia and OSMF. The OSCC group had a high mean total score of 7.90, followed by dysplasia at 5.40 and OSMF at 5.05. Conclusion: According to our research, there was a discernible pattern of elevated CD44 expression in OSCC relative to OSMF and dysplasia. These findings set the premise for further research to better outline the role of CD44 in the diagnosis of OSCC.